DINAMIKA MOTIVASI BELAJAR PAI SISWA PADA IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SMP NEGERI 1 JATI AGUNG - Andika, Rafi; Fatoni, Ahmad; Hasanah, Uswatun (Universitas Al-Amien Prenduan, 2025)
This study examines how students’ learning motivation in Islamic Religious Education (PAI) changes during the implementation of the Independent Curriculum at SMP Negeri 1 Jati Agung. In the field of Islamic education, this study examines how students’ motivation increases when the learning process becomes more active, flexible, and student-centered. This study aims to explain how students’ motivation changes., identify the factors that support and hinder motivation, and provide both theoretical and practical insights for developing adaptive PAI learning strategies. This study uses a qualitative approach, with data gathered through observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s steps of data reduction, data display, and verification. The findings indicate that students’ learning motivation increased progressively: initially passive during the adjustment phase, students gradually became more confident, participative, and enthusiastic in class discussions and learning activities. This increase was shaped by internal factors like interest, curiosity, and independence, as well as external factors such as the teacher’s teaching methods, creative learning media, school environment, peer influence, and parental support. Challenges such as low discipline, limited facilities, and variations in students’ religious competence were still present; however, these were mitigated through teacher guidance, communication with parents, and strengthened religious programs. This study helps improve PAI teaching practices by highlighting the importance of using diverse and meaningful learning strategies. The results show that the Independent Curriculum can effectively increase students’ motivation in PAI when it is supported by creative teaching methods and a supportive learning environment.